2020
DOI: 10.3390/genes11040360
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Lactobacillus crispatus from the Gut and Vagina Reveals Genetic Diversity and Lifestyle Adaptation

Abstract: Lactobacillus crispatus colonizes the human feces, human vagina, and the crops and ceca of chicken. To explore the genetic characteristics and evolutionary relationships of L. crispatus isolated from different niches, we selected 37 strains isolated from the human vagina (n = 17), human feces (n = 11), and chicken feces (n = 9), and used comparative genomics to explore the genetic information of L. crispatus from the feces and vagina. No significant difference was found in the three sources of genomic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 58 publications
4
26
0
Order By: Relevance
“…Generally, the vaginal microbiota is composed of a single and almost clonal population of Lactobacillus and L. crispatus CIP104459 may be an exception. In addition, this strain was isolated in 1955 and is, thus, old, whereas bacteria, including L. crispatus , can rapidly evolve in response to host 23 and environmental 24 factors, especially by rearrangements within their genomic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the vaginal microbiota is composed of a single and almost clonal population of Lactobacillus and L. crispatus CIP104459 may be an exception. In addition, this strain was isolated in 1955 and is, thus, old, whereas bacteria, including L. crispatus , can rapidly evolve in response to host 23 and environmental 24 factors, especially by rearrangements within their genomic structure.…”
Section: Discussionmentioning
confidence: 99%
“…crispatus is a biomarker for vaginal health, and some strains are used as probiotics against BV (Almeida et al 2019, Cohen et al 2020. Due to its association with health promotion, its genetic diversity and mechanisms involved in the probiotic effects of L. crispatus have been investigated using genomics data and in vitro experiments (Ojala et al 2014, Abdelmaksoud et al 2016, France et al 2016, Van der veer et al 2019, Pan et al 2020, Petit & Read 2020, Zhang et al 2020).…”
Section: Use Of Comparative Genomics In the Investigation Of Bvmentioning
confidence: 99%
“…Comparative genomics with a specific focus on vaginal isolates investigated the phylogeny, gene content, horizontal gene transfer, prophages, metabolism, and positive selection within strains (Ojala et al 2014, France et al 2016, Pan et al 2020, Petit & Read 2020, Zhang et al 2020. A comparison of strains from different hosts found that human vaginal isolates have a unique CRISPR Type II-A system, and a complete trehalose metabolism operon.…”
Section: Genomics Of L Crispatus Isolated From the Vaginamentioning
confidence: 99%
“…Comparative genomic analyses have been performed to identify genomic features of L. crispatus associated with female urogenital tract using samples from North America, Europe and Asia ( Ojala et al, 2014 ; Abdelmaksoud et al, 2016 ; France, Mendes-Soares & Forney, 2016 ; Van der Veer et al, 2019 ; Pan, Hidalgo-Cantabrana & Barrangou, 2020 ; Petit & Read, 2020 ; Zhang et al, 2020 ). Analyses that searched for genomic features associated with lactobacilli-dominated (healthy) or BV microbiota were performed using samples isolated from the USA ( Abdelmaksoud et al, 2016 ) and Netherlands ( Van der Veer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%